Knowledge, attitudes and practices (KAP) of selected hospitalized renal patients towards their diet implication for proper diet management - Bigsot, Emilia P. (Trinitian Researcher, 2013)
Therapeutic diet, which is modified in taste, restricted in the quantity and quality of foods allowed, is unpalatable and difficult to follow by chronic kidney patients; hence, making the patients nutritionally vulnerable. Adequate nutrition education is an important key to diet compliance. It is through knowing the right knowledge, the proper attitudes and practices that patients make appropriate food choices to maintain optimum health. This study measured the level of knowledge, attitudes and practices (KAP) of renal patients towards prescribed diets, the interrelationships among KAP and the relationships of KAP to selected demographic profile.